ABUNDANCE OF MASS 47 CO2 IN URBAN AIR, CAR EXHAUST, AND HUMAN BREATH - Affek H.P.; Eiler J.M. (My University, 2006)
Atmospheric carbon dioxide is widely studied using records of CO2 mixing ratio, δ13C and δ18O. However, the number and variability of sources and sinks prevents these alone from uniquely defining the budget. Carbon dioxide having a mass of 47 u (principally 13C18O 16O) provides an additional constraint. In particular, the mass 47 anomaly (Δ47) can distinguish between CO2 produced by high temperature combustion processes vs. low temperature respiratory processes. Δ47 is defined as the abundance of mass 47 isotopologues in excess of that expected for a random distribution of isotopes, where random distribution means that the abundance of an isotopologue is the product of abundances of the isotopes it is composed of and is calculated based on the measured 13C and 18O values. In this study, we estimate the δ13C (vs. VPDB), δ18O (vs. VSMOW), δ47, and Δ47 values of CO2 from car exhaust and from human breath, by constructing 'Keeling plots'using samples that are mixtures of ambient air and CO2 from these sources. δ47 is defined as (R47/ Rstd47 - 1) × 1000, where Rstd47 is the R47 value for a hypothetical CO2 whose δ13CVPDB = 0, δ18OVSMOW = 0, and Δ47 = 0. Ambient air in Pasadena, CA, where this study was conducted, varied in [CO2] from 383 to 404 μmol mol-1, in δ13C and δ18O from -9.2 to -10.2‰ and from 40.6 to 41.9‰, respectively, in δ47 from 32.5 to 33.9‰, and in Δ47 from 0.73 to 0.96‰. Air sampled at varying distances from a car exhaust pipe was enriched in a combustion source having a composition, as determined by a 'Keeling plot'intercept, of -24.4 ± 0.2‰ for δ13C (similar to the δ13C of local gasoline), δ18O of 29.9 ± 0.4‰, δ47 of 6.6 ± 0.6‰, and Δ47 of 0.41 ± 0.03‰. Both δ18O and Δ47 values of the car exhaust end-member are consistent with that expected for thermodynamic equilibrium at ~200 °C between CO2 and water generated by combustion of gasoline-air mixtures. Samples of CO2 from human breath were found to have δ13C and δ18O values broadly similar to those of car exhaust-air mixtures, -22.3 ± 0.2 and 34.3 ± 0.3‰, respectively, and δ47 of 13.4 ± 0.4‰. Δ47 in human breath was 0.76 ± 0.03‰, similar to that of ambient Pasadena air and higher than that of the car exhaust signature. © 2005 Elsevier Inc. All rights reserved.